Educational Experience in the Mobile Learning Environment: Consumer Behavior Perspective - Volkovitckaia, Galina; Tikhonova, Yuliya; Kolosova, Olga (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The development of digital technologies necessitates the formation of digital literacy and entrepreneurship skills in the modern "digital generation". The study has as the objective to identify the aspects of consumer demand for educational services in the process of testing the conceptual model of mobile learning adapted to the modern business environment in the context of digital transformations of the socio-economic life. The concept of an educational course based on the Sakai mobile learning platform with a focus on the formation of digital literacy in the business segment has been proposed in the study. The educational and applied course "Entrepreneurship in the Digital Mode" was tested within the educational programs of the State University of Management (Lyubertsy, Russia) and Herzen State Pedagogical University of Russia (St. Petersburg, Russia). The experiment made it possible to identify key aspects of consumer demand for distance education based on the characteristics of the participants' perception of the advantages and effectiveness of mobile learning. Most participants confirmed their professional achievements and the fact of the implementation of personal educational goals. Mobile learning was described as an easy, comfortable, interesting, innovative and modern method of learning compared to traditional classroom lessons. In the process of mobile learning, students demonstrated an increase in personal responsibility and self-organization while practical classes and the synergy of the educational content with real business cases greatly contributed to their involvement and productivity. Until now, research has not dealt with real measurable in terms of real income from specific activities, the results of the application of mobile learning. The contribution of this study to the area under study is to establish pedagogical demands that can be satisfied with mobile learning.